Portrait Of Political Culture In A Multicultural Society In Padang City: A Case Study: Change Of "Kampung Jao" To "Kampung Jawa" In Padang Barat District, Padang City - Irwan, Irwan; Zusmelia, Zusmelia; Nurrahma, Epriwina Gini; Rahmona, Maulana; Nefilinda, Nefilinda (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The pattern of political culture that occurs in Java Village between the government and the community has different perceptions.  This causes an unbalanced and idealized view. The purpose of this research is to analyze the portrait of political culture in a multicultural society in the change of "Kampung Jao" to "Kampung Jawa" in Padang Barat District, Padang City. This research uses the theory put forward by Sydney Verba, where political culture refers more to the orientation of all members in the group of a system in politics.  The research method uses a qualitative approach with descriptive research type. The data collection method begins with participant observation, in-depth interviews, and documents. Data analysis using the Miles and Huberman model. The results of this study show that the portrait of political culture in naming the Javanese village area does not involve the local community as the indigenous population. In addition, there is an imbalance of political culture both by those who have the authority (government and society). In addition, the life of the community experienced different ideas or perceptions regarding the change of the name of Jao village to Javanese village. Based on the research results, it can be concluded that the political culture between the government and society is not yet included in the category of a balanced and ideal political culture because there is still selfishness on the part of each party, both the government, who feel they have position and power, so that in making decisions they do not include the people or society in it, as well as those in the community who did not pay close attention to changing the name of Kampung Jao to Kampung Jawa.